2011
DOI: 10.1042/cs20110043
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic variability affects ischaemia-induced angiogenesis in diabetic mice

Abstract: The aim of the present study was to investigate the role of GV (glycaemic variability) in diabetic vascular complications and to explore the molecular pathways modulated by glycaemic 'swings'. We developed a murine model. A total of 30 diabetic mice received once daily basal insulin administration plus two oral boluses of glucose solution (GV group, named 'V') and 30 diabetic mice received once daily basal insulin plus two oral boluses of saline solution (stable hyperglycaemia group, named 'S') for a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…At present, research into the effect of glycemic oscillations on influenza severity is limited by the lack of an appropriate animal model of glycemic variability. Glycemic spikes have been studied in mice through repeated administration of a glucose/ maltose bolus (24)(25)(26)(27). Alternatively, glycemic variability has been modeled using glucose injections in rats fed a high-fat diet (HFD) (28).…”
mentioning
confidence: 99%
“…At present, research into the effect of glycemic oscillations on influenza severity is limited by the lack of an appropriate animal model of glycemic variability. Glycemic spikes have been studied in mice through repeated administration of a glucose/ maltose bolus (24)(25)(26)(27). Alternatively, glycemic variability has been modeled using glucose injections in rats fed a high-fat diet (HFD) (28).…”
mentioning
confidence: 99%
“…Despite similar baseline clinical characteristics-in terms of risk factor control and PAD severity-and the same endovascular approach, some patients do not encounter complications for years while other patients may have complications, even fatal, within a few months [26]. Several potential biomarkers have been proposed, some linked to patient's genetic characteristics [25,[27][28][29], many linked metabolic and in ammatory parameters [19,25,[30][31][32][33]. Among the possible candidates, the pathways linked to adipose tissue represent a promising eld of study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diabetes -induced renal damage is also amplifi ed by a signifi cantly blunted ECM turnover, largely through reductions of MMP activity [ 121 ]. Hyperglycemia has been shown to play a deleterious role on the function of cell progenitors [ 122 ] and on the VEGF-eNOS pathway, leading to impairment of the angiogenic response [ 123 ]. In the kidney, it has been suggested that hyperglycemia is initially associated with high but ineffective VEGF signaling that translates into a progressive MV dysfunction and damage in early diabetes [ 124 , 125 ].…”
Section: Renal Microvascular Disease In Diabetesmentioning
confidence: 99%
“…Importantly, there is abundant experimental evidence that treatments that blunt fi brosis can also blunt vascular rarefaction, and vice versa [ 108 ]. In this context, targeting infl ammation and the resultant oxidative stress with an agent such as bindarit, which inhibits production of monocyte chemoattractant protein-1, may be a useful therapeutic approach [ 123 ].…”
Section: Clinical Implications/therapymentioning
confidence: 99%